Anticoagulation after pulmonary vein isolation for atrial fibrillation: Associations with CHA₂DS₂‐VASc score, sex, and rhythm. (7th February 2023) - Wang, Tom Kai Ming; Chan, Nicholas; Arockiam, Aro D.; Cremer, Paul C.; Kanj, Mohamed; Baranowski, Bryan; Saliba, Walid; Hussein, Ayman; Wazni, Oussama M.; Jaber, Wael A.; ,
Abstract: Guidelines recommend using the CHA₂DS₂‐VASc score to determine anticoagulation decisions in atrial fibrillation (AF) patients, including those who undergo pulmonary vein isolation (PVI), however this may not consistently occur in the real‐world setting because of other clinical factors. We sought to evaluate the anticoagulation prescription rates patterns in AF patients 1 year PVI at our institution. Consecutive AF patients undergoing PVI in our prospective registry during 2014−2018 who were alive at 1‐year post‐PVI were studied. Anticoagulation prescription rates at this time‐point were adjudicated, and correlated to CHA₂DS₂‐VASc score, sex, and heart rhythm status at 1 year. Amongst 4596 patients undergoing PVI, mean age was 64.2 ± 10.0 years, 1328 (28.9%) were female, and based on CHA₂DS₂‐VASc score anticoagulation was not indicated, can be considered and indicated in 872 (19.0%), 1183 (25.7%), and 2541 (55.3%) patients, respectively. At 1‐year after PVI, 3504 (76.2%) patients were on anticoagulation, and 792 (17.2%) had recurrence of AF. Anticoagulation was continued in over half of AF patients without classic CHA₂DS₂‐VASc indication particularly in those with AF recurrence and women, while they were mildly under‐prescribed in those with indication, especially for those without AF recurrence and men. In a large real world cohort of patients after PVI, anticoagulation prescription is not solely depending on the CHA₂DS₂‐VASc score and sex, but also heart rhythm status and other clinical or imaging factors.